Is the Effectiveness of Self-Visualization During Flexible Cystoscopy Gender-Dependent in Patients with no Previous Cystoscopy History? A Prospective Randomized Study - Nurullah Hamidi; Mehmet Duvarci; Tuncel Uzel; Oguzhan Ceylan; Serhat Haluk Unal; Erdem Ozturk (International Brazilian Journal of Urology)
ABSTRACT Purpose: To evaluate the effect of real-time self-visualisation (SV) of the procedure during flexible cystoscopy (FC) on pain and anxiety in male and female patients with no prior cystoscopy history. Patients and Methods: Between Dec 2022-May 2024, 400 patients who underwent office-based FC were enrolled into prospective randomized study in accordance with CONSORT. Patients were randomised into two groups (SV and no-SV) using sequential (1:1 ratio) randomisation. To ensure equal numbers of male and female patients in each group, one consecutive male patient was assigned to the SV group, while the next male patient was assigned to the non-SV group; the same randomization was done for females. The primary endpoint was to evaluate the pain during FC (during urethral insertion of the cystoscope and bladder examination stages) of both groups. The secondary endpoint was to evaluate anxiety, patient satisfaction, and willingness to undergo the procedure of both groups. Results: In males, significant lower pain scores were detected in SV group during urethral insertion of the cystoscope (1.4 vs. 4.8, p<0.001) and during bladder examination (0.9 vs. 3.1, p<0.001). However, pain scores during urethral insertion of the cystoscope (1.9 vs. 2, p=0.38) and during bladder examination (1.2 vs. 1.3, p=0.63) were statistically similar between two groups in female patients. In both genders, significant lower anxiety levels, higher patient satisfaction and higher willingness to undergo repeat cystoscopy were detected in SV group. Conclusion: SV during FC may be beneficial in reducing pain in male patients but not in female patients. SV during FC has a positive effect on anxiety, patients’ satisfaction, and willingness to undergo repeat procedures, regardless of gender.